Analisis Pengaruh Faktor Kepercayaan dan Resiko pada Niat Perilaku Konsumen Dalam Bertransaksi Menggunakan Online Ticket Agent XYZ - Nurma Abadi Firjatulloh; Ari Kusyanti; Himawat Aryadita (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
E-Commerce is a business transaction activity conducted by utilizing the technology of the Internet network or so-called online transactions. Currently the ticket sales industry or travel agent also utilizes online sales transactions. One of the companies in Indonesia that also take advantage of online business transactions that is Online Ticket Agent XYZ. Online Ticket Agent XYZ is one of the e-commerce sites in the field of ticket sales or the largest travel agency in Indonesia. Although online transactions are increasingly in demand, this type of transaction is not always safe and even vulnerable to fraud. There have been some consumer reports of Online Ticket Agent XYZ who feel harmed while transacting using the site, things like this can affect consumer confidence to make transactions using Online Ticket Agent XYZ site. This study proposes a model based on three previous research journals consisting of 16 variables. The analysis method used in this research is Partial Least Square (PLS). The results of this study indicate that consumer confidence (Consumer Trust) and perceived risk of consumer (Perceived Risk) affect the intention of consumers to transact (Intention to Purchase) using Ticket.com site.